IMPLEMENTASI PERLINDUNGAN HUKUM HAK ATAS KEKAYAAN INTELEKTUAL (HKI) PADA INDUSTRI KECIL MENENGAH (IKM) BATIK TRADISIONAL PACE DI KABUPATEN PACITAN - Arkananta, Sandya Rafi (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
Intellectual Property Rights (IPR) is a form of ownership held by individuals as a result of their intellectual abilities or intelligence. One example of intellectual property is traditional pace batik. This batik has a unique motif, as it uses patterns derived from images of the pace fruit or morinda, which hold historical evidence and significance for Pacitan Regency. It is essential to preserve, safeguard, and protect this uniqueness by various parties. The purpose of this research is to determine the efforts of the Pacitan Regency Local Government in facilitating legal protection of intellectual property rights (IPR) and identifying constraints while finding effective solutions in implementing legal protection of intellectual property rights (IPR) in the traditional pace batik small and medium-sized enterprises (SMEs) industry in Pacitan Regency. The research approach used is juridical-empirical, utilizing primary data sources obtained directly from the main sources in the field. The findings of this research indicate that the implementation of legal protection of Intellectual Property Rights (IPR) in the Small and Medium-sized Enterprises (SMEs) of traditional pace batik industry has not been effectively executed due to the incomplete coverage of the efforts by the government for the entire industry, constraints from the Pacitan Regency Local Government or related agencies, and challenges faced by the traditional pace batik SMEs, influenced by various factors such as the economy and lack of awareness of the law. These constraints can be overcome by maximizing the existing legal efforts or solutions